ASOSIASI GLUKOSA DARAH, STATUS GIZI, MOOD DAN LAMA MENDERITA DIABETES TERHADAP TEKANAN DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Cita, Errick Endra; Yuanita, Yuanita (Universitas Tribhuwana Tunggadewi, 2022)
The percentage of diabetes incidence increased from 6.9% to 8.5% in Indonesia starting from 2013 to 2018. In 2012 the mortality rate due to diabetes was 1.5 million deaths. Hyperglycemia above the threshold increases 2.2 million deaths and the risk of cardiovascular disease. DM caused 1.5 million deaths in 2012. Blood sugars higher than the upper limit resulted in an additional 2.2 million deaths, increasing the risk of cardiovascular disease. Blood pressure patterns change during the development of hypertension in patients with or without diabetes mellitus. Diabetes mellitus and hypertension often occur together. Knowing the common causes and mechanisms of disease allows for a more effective and proactive approach to its prevention and treatment. The purpose of this study was to identify the relationship of blood glucose, nutritional status, mood and length of suffering in patients with Type II Diabetes Mellitus (DM Type II) to blood pressure. The research instruments used were Blood glucose monitoring system GE100, Spygnomanometer (Automatic Blood Pressure Monitor HEM-7130), weight scales, height measuring devices and FACES Test. The study used a cross-sectional correlational quantitative method with a consecutive sample technique of 51 diabetic patients. Spearman's test is used in this research. The results of the correlation test with the significance value of p are 0.000 and 0.004 . Blood Glucose Levels and Mood/mood have a correlation with blood pressure and have a strong and moderate correlation strength. Further research is needed to holistically identify changes in blood pressure in patients with diabetes.